The effects of selected improving methods on wrinkle resistance of warp knitted and laminated car seat cover fabrics. (September 2014) - Deǧirmenci, Züleyha; Çelik, Nihat
This article investigates the effects of selected finishing methods on wrinkle resistance of laminated and non-laminated car seat cover fabrics. This study was carried out on five types of fabrics that have different properties. Apart from the reference fabric that is commonly manufactured in the automobile industry, four fabrics were produced using four different methods. All sample fabrics were knitted with a three-bar tricot machine at a conventional mill under the same conditions. As seat cover fabrics are generally laminated, sample fabrics were tested as laminated and non-laminated in order to investigate the effect of lamination. Samples were laminated with polyurethane and another warp knitted fabric that was knitted with a two-bar tricot machine and served as a lining. During the study, the wrinkle resistances of 10 laminated and non-laminated fabrics were measured at regular intervals. When the findings of the study were analyzed graphically and statistically, the method of using softening agent at foulard was found to be the most convenient one to produce high wrinkle resistant seat cover fabrics.